The Influence of Legislative Regulations on Serdang Berdagai’s Public Service - Zidan Ridwan Nur; Nurbaiti Nurbaiti (International Journal Labs, 2021)
In reality, the implementation of public services is a mandate given by the community to state or government administrators (executives and legislatures) whose purpose is to improve the welfare of the community. The purpose of this study was to prove and analyze the influence of the Serdasng Berdagai DPRD Policy on Public Sector Services in Kec. Serdang Berdagai. The method used in this research is a survey method with a quantitative approach. The population of this research is the people of Kec. Serdang Berdagai. The results showed that the policy of the Serdang Berdagai DPRD had a positive and significant effect on public sector services in the district. Serdang Berdagai. Likewise, the description of the results of the Serdang Berdagai DPRD's policy shows very good results and the correlation value of the Serdang Berdagai DPRD's policy on Public Sector Services has a strong value and also a strong position.